Dachaihu decoction ameliorates abnormal behavior by regulating gut microbiota in rats with propionic acid-induced autism - Zhang, Yangyang; Li, Hang; Li, Bolin; Li, Yizhuang; Chai, Xuejun; Li, Sheng; Xue, Xia; Li, Honglei; Zhao, Yonghong; Tang, Youcai; Yin, Baoqi; Zhao, Pengju; et al. (Frontiers in Microbiology, 2025)
BackgroundAutism spectrum disorder (ASD) is an early-onset neurodevelopmental disorder, usually accompanied by gut microbiota dysregulation. Gut microbiota homeostasis is considered effective for ASD. Reportedly, Dachaihu decoction (DCHD) can efficiently regulate gut microbiota and inflammation. However, the mechanisms underlying the effects of DCHD in the treatment of ASD remain unclear.ObjectiveThis study investigated the potential effects and mechanisms of DCHD in treating ASD.MethodsIn the animal experiment, propionic acid was administered to construct an ASD rat model. The ASD rats were treated with DCHD, and the efficacy was assessed using the behavioral detections, such as open field test, elevated plus maze test, novel object recognition test. Additionally, the levels of IL-6, TNF-α, IL-10, T-SOD, MDA, GSH and CAT were determined using kits, and histological staining was used to evaluate brain morphology. Moreover, tight junction proteins (ZO-1 and occludin) expression levels were evaluated using RT-qPCR, whereas Iba1 expression level was assessed by immunofluorescence staining. The 16S rRNA sequencing and metabolomic analysis of feces revealed the potential targets of DCHD against ASD. In a small human trail, the clinical scales ADOS-2 and Autism Behavior Checklist (ABC) assessed autism severity. Gastrointestinal problems and brain function were evaluated based on food intolerance and event-related potential, respectively.ResultsDCHD significantly improved autism-like behaviors and increased antioxidant enzyme activity, decreased inflammation and enhanced the intestinal barrier by the animal experiment. Furthermore, the DCHD treatment altered the gut microbiota profile, with increased probiotics Adlercreutzia, Parvibacter, Turicibacter, and Christensenellaceae. Further, DCHD increased the beneficial metabolite indole-3-acetate and decreased the cognitive impairment-related metabolites asymmetric dimethylarginine and homogentisic acid. Meanwhile, the small clinical trial revealed that DCHD significantly alleviated the core symptoms of ASD, with decreased ADOS-2 and ABC scale scores. DCHD also decreased the levels of specific egg white/yolk and milk IgG antibodies and shortened the MMN and P3b latencies.ConclusionThis study demonstrated that DCHD may alleviate ASD via inhibiting oxidative stress, reducing inflammation, and modulating the gut microbiota in rats. Combined with human trial, DCHD may be a promising drug for treating ASD. This study provides a scientific rationale for treating mental disorders related to gut microbiota dysbiosis.